Oriental Motifs in the Painting of Oleksandr Zhyvotkov (1990s–2020s) - Guo, Jingyuan (HUDPROM: The Ukrainian Art and Design Journal, 2024)
Oriental motifs are one of the most distinctive features in the painting of Oleksandr Zhyvotkov, often leading to his classification as an “oriental” artist. At the same time, his work represents a unique artistic vision shaped by Eastern culture and philosophy. This article aims to explore the presence of oriental motifs in Zhyvotkov’s painting throughout the key stages of his career (1990s–2020s). The research methodology involves comparative, typological, chronological, and figurative-stylistic analysis. Zhyvotkov’s early period is characterized by an emphasis on simple forms and minimal texture, especially in contrast with his works from the 2010s–2020s. Although the artist himself does not explicitly highlight oriental influences, his imagery speaks for itself. A comparison with Chinese avant-garde and minimalist artists of the same period – primarily Chen Wenji (陈文骥) and Li Shouyu (林壽宇) – reveals a shared approach to artistic form and means of expression. This unconscious alignment stems from the abstract art traditions of the East and the Taoist pursuit of a minimalist, “calm,” and “balanced” aesthetic. The “Eastern” phase of Zhyvotkov’s work in the 2000s–2010s marks a significant conceptual expansion. During this period, he not only embraces fundamental Eastern ideas such as tranquility, space, and purification but also introduces narrative elements into his paintings. This shift, in our view, reflects his deepening artistic reinterpretation of Eastern philosophy. Zhyvotkov’s current work continues to engage with oriental themes, integrating universal artistic approaches with his own symbolic language. Concepts drawn from Eastern philosophy – particularly Zen and Taoist principles of calmness, proportionality, and the fluidity of consciousness – remain an essential part of his visual language.